Genetic polymorphism of KIR2DL4 (CD158d), a putative NK cell receptor for HLA‐G, does not influence susceptibility to asthma. Issue 4 (23rd August 2013) - Le Page, M. E. L.; Goodridge, J. P.; Zhang, G.; Holt, P. G.; Sly, P.; Witt, C. S.
Abstract Human leukocyte antigen (HLA)‐G is upregulated on the bronchial epithelium of asthma patients and genetic polymorphism affecting expression of HLA‐G has been reported to influence susceptibility to asthma. As the NK cell receptor KIR2DL4 has been reported to induce interferon gamma (IFNγ) secretion when ligated with HLA‐G, we postulated that the 9A/10A genetic polymorphism of KIR2DL4 which influences receptor structure may influence susceptibility to asthma. KIR2DL4 genotypes were determined in two cohorts of children (n = 219 and n = 1356) in whom total serum IgE, allergen‐specific IgE, atopy, bronchial reactivity and asthma symptoms had been studied between birth and 14 years. No reproducible associations with KIR2DL4 genotype were identified, leading us to conclude that the KIR2DL4 9A/10A polymorphism has no influence on susceptibility to asthma.